Transmembrane signal transduction by peptide hormones via family B G protein-coupled receptors - Culhane, Kelly J.; Liu, Yuting; Cai, Yingying; Yan, Elsa C. Y. (Frontiers in Pharmacology, 2015)
Although family B G protein-coupled receptors (GPCRs) contain only 15 members, they play key roles in transmembrane signal transduction of hormones. Family B GPCRs are drug targets for developing therapeutics for diseases ranging from metabolic to neurological disorders. Despite their importance, the molecular mechanism of activation of family B GPCRs remains largely unexplored due to the challenges in expression and purification of functional receptors to the quantity for biophysical characterization. Currently, there is no crystal structure available of a full-length family B GPCR. However, structures of key domains, including the extracellular ligand binding regions and seven-helical transmembrane regions, have been solved by X-ray crystallography and NMR, providing insights into the mechanisms of ligand recognition and selectivity, and helical arrangements within the cell membrane. Moreover, biophysical and biochemical methods have been used to explore functions, key residues for signaling, and the kinetics and dynamics of signaling processes. This review summarizes the current knowledge of the signal transduction mechanism of family B GPCRs at the molecular level and comments on the challenges and outlook for mechanistic studies of family B GPCRs.